2020
DOI: 10.1007/s00701-020-04247-3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and complication rates of external ventricular drain placement with twist drill and bolt system versus standard trephine and tunnelation: a retrospective population-based study

Abstract: Background An external ventricular drain (EVD) is typically indicated in the presence of hydrocephalus and increased intracranial pressure (ICP). Procedural challenges have prompted the development of different methods to improve accuracy, safety, and logistics. Objectives EVD placement and complications rates were compared using two surgical techniques; the standard method (using a 14-mm trephine burrhole with the EVD tunnelated through the skin) was compared to a less invasive method (EVD placed through a 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
3
12
2
Order By: Relevance
“…Due to the high frequency of ventriculostomy in neurosurgical practice, complications resulting from failed puncture or inadequate anatomical position are relatively common. 13 To improve precision, technical tools such as neuronavigation can be employed. 14 Despite strong evidence that freehand ventriculostomy has been identified as a risk factor for malposition of ventricular catheters, 15 a survey showed that neurosurgeons would be reluctant to use technical help if the time expense exceeded 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high frequency of ventriculostomy in neurosurgical practice, complications resulting from failed puncture or inadequate anatomical position are relatively common. 13 To improve precision, technical tools such as neuronavigation can be employed. 14 Despite strong evidence that freehand ventriculostomy has been identified as a risk factor for malposition of ventricular catheters, 15 a survey showed that neurosurgeons would be reluctant to use technical help if the time expense exceeded 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Bolt EVDs are gaining increasing acceptance over the traditional burr-hole technique among both the neurosurgical and neuro-intensive care communities. This is following a number of reports over the past years that have demonstrated their more favourable rate of procedure-related complications [2,3,17] (or, at the least, comparable to that of traditional external ventriculostomy [16,12]). Furthermore, bolt EVDs placed in ICU impart a non-measurable logistical and medical advantage by avoiding transfer of potentially unstable patients to the operating theatre.…”
Section: (1) Bolt Evd Insertion In Icumentioning
confidence: 70%
“…However, bolt EVDs come with their own unique challenge, notably the limited possibility for correcting errors in trajectory [12]. This is in contrast to the traditional technique where a change in catheter trajectory is possible if the initial attempt at reaching the ventricle is unsuccessful, owing to the burr-hole's relatively larger diameter.…”
Section: Introductionmentioning
confidence: 99%
“…5,15,16 Results are also influenced by the system used to rate success. 17,18 Our experiments were not conducted in patients, which makes direct comparison to the literature difficult. However, the raw numbers in this study reflect success rates described in previous studies.…”
Section: Discussionmentioning
confidence: 99%